The Effect of Contact Time Variations of Activated Carbon from Coconut Shell on the Peroxide Value in Used Cooking Oil - Djohan, Herlinda; Sungkawa, Hendra Budi; Chitra, Fara; Ningsih, Nur Reza (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Cooking oil is a commonly used food product in daily life, both in households and commercially, especially for frying purposes. The repeated use of cooking oil can lead to an increase in peroxide value, which may pose health risks. High peroxide values are carcinogenic and can trigger various health problems, such as elevated cholesterol levels and heart disease. One method to reduce peroxide value is by using activated carbon, such as activated carbon derived from coconut shells. This study aims to analyze the effect of contact time variations of activated carbon from coconut shells on the reduction of peroxide value in used cooking oil. The research design used was a quasi-experiment with an iodometric testing method. A total of 24 samples of used cooking oil were treated with activated carbon from coconut shells for different contact times: 20 minutes, 30 minutes, and 40 minutes. The peroxide value was then measured. The results showed that varying the contact time with activated carbon from coconut shells resulted in the following average peroxide values: 15.57 meq O2/kg, 7.57 meq O2/kg, 6.58 meq O2/kg, and 5.82 meq O2/kg. The percentage reduction in peroxide value was 0%, 51.41%, 57.06%, and 62.64%, respectively. In conclusion, the study found a significant effect of contact time variations of activated carbon from coconut shells on the reduction of peroxide value in used cooking oil, with a probability value of 0.000 < 0.05.